Hubungan Riwayat Paparan Pestisida dengan Kejadian Gangguan Fungsi Hati (Studi Pada Wanita Usia Subur di Daerah Pertanian Kota Batu) - Jenni, Ashanur; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2014)
Background: The woman of childbearing-age is one of the population at risk for pesticide poisoning with long term negative effects. Negative effects of pesticides exposureÂ in woman of childbearing-age can cause liver disfunction. The objective of this research was to analize the assosiation between pesticides exposure and liver disfunction on women childbearing-age at Kota Batu. Methods: This research is an analytical study using cross-sectional approach. The research took sample 165 women in childbearing-age from four villages which were chosen purposively. Data obtained from research data specific environmental pollutionin agricultura lregions Kota Batu conducted by the Agency for Health Research and Development of the Ministry of Healthin 2012. Results:The results showed that the average at childbearing-age women in the agricultural zone in Batu was 37.41Â± 8.704 years, with the number of women of childbearing-age who had detect able pesticide exposure were 55 people (33.3%). Further more, by multivariate analysis using the test Structural Equation Modeling (SEM) found a significant relationship betweena history of exposure to pesticides with the incidence of liver dysfunction with a coefficient value of 0.242 and the value of the T-Statistic test of 2,615 women of childbearing-age in Kota Batu. Conclusion: women of childbearing-age who experiencedliver dysfunction was 70.9% of the 55 people had pesticides exposure. To avoidliver dysfunction, It is suggested to better knowledge of storage, formulation of pesticide and washing the families farmers clothes Keywords: women of childbearing-age, pesticides exsposure, liver dysfunction